If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4y + -2z = 6 Solving 2x + 4y + -2z = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 2x + 4y + -4y + -2z = 6 + -4y Combine like terms: 4y + -4y = 0 2x + 0 + -2z = 6 + -4y 2x + -2z = 6 + -4y Add '2z' to each side of the equation. 2x + -2z + 2z = 6 + -4y + 2z Combine like terms: -2z + 2z = 0 2x + 0 = 6 + -4y + 2z 2x = 6 + -4y + 2z Divide each side by '2'. x = 3 + -2y + z Simplifying x = 3 + -2y + z
| 0.42x-5=4 | | x+3y-z=12 | | 5x-y+5z=30 | | 5x-2x+6-4+14=5x-3x+8 | | 3(g-7)-2=4 | | 16=-4-4x | | -x+2y-3z=-9 | | -3t+5=26 | | 4x-2x+3-8=7x-5+4x | | 3t+5=26 | | (x^2+y^4)(x^2-y^4)=0 | | 0.67x+7=21 | | 72+36=0 | | 5x-2+8=7x-4 | | 21=8x-75 | | 6a+5x=36 | | (4s+4)(4s-4)=0 | | 3x+y+z=14 | | (3r-1)(4r-3)=0 | | 15-8m=73 | | -8x+6x-7x=3x(4-3)-5x-15 | | 98p=197 | | 5/3= | | 170-2x=25x+20 | | -5=15+4x | | 5x-x+3=-x+7 | | 5-9x=37-16x | | 3n+4=56 | | 3(4i)+2(7i)= | | 3(2x-3)-2x=8-2(3x+1) | | 5x-8-3x-9=-12x+11 | | y^2+4x-4y-12=0 |